Comparison of Vault Measurements Using a Swept-Source OCT-Based Optical Biometer and Anterior Segment OCT - Du, Yali; Jin, Chuang; Yin, Shengjie; Wang, Geng; Ma, Qian; Li, Yuancun; Chen, Binyao; Wang, Hongxi; Qiu, Kunliang; Zhang, Mingzhi (Frontiers in Medicine, 2022)
Background: To newly describe the vault measurement by using a widely used swept-source OCT-based optical biometer (IOLMaster700) and accessd the accuracy of vault measurement using IOLMaster700. Methods: This was a retrospective, cross-sectional study. All patients underwent implantable Collamer lens (ICL) implantation surgery without complications. IOLMaster700 and AS-OCT analyses were conducted for each eye on the same day in the same room. Measurements of anterior chamber depth (ACD), corneal-ICL (C-ICL), and vault values were made and recorded, after which correlations between the measurements made with these different analytical approaches were assessed. The correlation between and agreement of instruments was evaluated using intraclass correlation coefficient (ICC) values and Bland-Altman plots. Results: The IOLMaster700 instrument yielded highly reliable measurements of vault, C-ICL, and ACD (ICC=0.996, 0.995, 0.997, respectively), with no significant differences in vault measurements between the two devices (p=0.094). The vault, C-ICL, and ACD measurements for these two instruments were strongly correlated (r=0.961, r= 0.888, and r=0.894, respectively; all p< 0.001). The 95% limits of agreement for vault, C-ICL, and ACD measurements between the two devices were -0.10 to 0.07 mm, -0.37 to -0.06mm, and -0.24 to 0.10mm, respectively. Conclusions: The analyzed swept-source OCT-based optical biometer can measure implanted ICL vault with a high degree of accuracy and repeatability. Good correlations and agreement were observed between IOLMaster700 and AS-OCT measures of vault, C-ICL, and ACD measurements.